2002
DOI: 10.1002/ijc.10299
|View full text |Cite
|
Sign up to set email alerts
|

Local photodynamic therapy (PDT) of rat C6 glioma xenografts with Pd‐bacteriopheophorbide leads to decreased metastases and increase of animal cure compared with surgery

Abstract: Photodynamic therapy (PDT), locally applied to solid C6 rat glioma tumors in the foot of CD1 nude mice, eradicated the primary tumor and also decreased the rate of groin and lung metastases. Pd-Bacteriopheophorbide (Pd-Bpheid), a novel photosensitizer synthesized in our laboratory, was used in our study. The primary lesion in the hind leg was treated by an i.v. injection of 5 mg/kg of Pd-Bpheid and immediate illumination (650 -800 nm, 360 J/cm 2 ). This protocol and the surgical amputation of the leg were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 24 publications
2
76
0
Order By: Relevance
“…Some reports have shown that PDT can markedly inhibit distant metastasis of tumors in vivo (10,20,31), while others suggest that PDT can facilitate metastasis (31). In this research we did observe distant metastasis and blood vessel infiltration under the microscope in tumor tissue, indicating the metastatic characteristic behavior of CNE2 cells after ALA-PDT.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Some reports have shown that PDT can markedly inhibit distant metastasis of tumors in vivo (10,20,31), while others suggest that PDT can facilitate metastasis (31). In this research we did observe distant metastasis and blood vessel infiltration under the microscope in tumor tissue, indicating the metastatic characteristic behavior of CNE2 cells after ALA-PDT.…”
Section: Discussionsupporting
confidence: 53%
“…In the preliminary study we found that nude mice bearing CNE2 NPC tumors have distant metastasis following 5-ALA (aminolevulinic acid)-PDT (data not shown). However, reports from several other laboratories suggest that PDT decreases metastasis compared to results obtained with surgery (19,20). Following in vitro HPD (hematoporphyrin)-based PDT, adhesion to extracellular matrix (ECM) and metastatic potential declined in DHD-K12-cultured colon carcinoma cells (21), and the same research group observed similar results in vivo (22).…”
Section: Introductionmentioning
confidence: 86%
“…To address this hypothesis the effect of PDT treatment of s.c. tumours on the growth of established lung tumours in immuno-competent mice bearing concomitant s.c. and lung tumours was examined. Previous studies that have examined the effect of local PDT on distant tumours have done so in the absence of an intact immune system (Schreiber et al, 2002), were unable to detect control of distant disease (van Duijnhoven et al, 2003), performed PDT before establishment of distant tumours (Momma et al, 1998), or have not discerned a mechanism by which PDT inhibits the growth of tumours outside the treatment field (Gomer et al, 1987;Blank et al, 2001;Castano et al, 2003). In the current study, we demonstrate that control of the growth of tumours present outside the treatment field is dependent upon an intact immune system, is mediated by CD8 þ T cells and is accompanied by induction of anti-tumour immune memory responses.…”
mentioning
confidence: 99%
“…Established methods were used to test for enhanced lung metastasis, which have been used for the study of metastasis resulting from therapeutic or diagnostic manipulation of tumors implanted on the hind leg. 11,[20][21][22] A suspension of 1 million cells in 0.05 mL was injected subcutaneously on the right hind leg of each mouse under ether anesthesia. Treatment was applied after 10 days of tumor growth.…”
Section: Methodsmentioning
confidence: 99%